2021
DOI: 10.1101/2021.02.16.431432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organic electron donors and terminal electron acceptors structure anaerobic microbial communities and interactions in a permanently stratified sulfidic lake

Abstract: The extent to which nutrients structure microbial communities in permanently stratified lakes is not well understood. This study characterized microbial communities from the anoxic layers of the meromictic and sulfidic Fayetteville Green Lake (FGL), NY, and investigated the roles of organic electron donors and terminal electron acceptors in shaping microbial community structure and interactions. Bacterial communities from the permanently stratified layer below the chemocline (monimolimnion) and from enrichment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 121 publications
1
10
0
Order By: Relevance
“…We found that each well had a distinct microbial composition with various sulfur‐reducing (or H 2 S‐producing) bacteria as well as other archaea and bacteria found in previous MEOR studies 17,41 . Common bacteria phyla include Proteobacteria, Bacteroidota, Firmicutes, Synergistota, Spirochaetota, Verrucomicrobiota, Desulfobacterota, and Campilobacterota, of which the latter three are prominent sulfur‐metabolizing bacteria 42–45 . These populations were distinct from others in the literature, 13,37 a finding that is not unexpected given that each community is driven by un environmental conditions such as temperature, salinity, pH, nutrient availability, and oil gravity among other factors 25 .…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…We found that each well had a distinct microbial composition with various sulfur‐reducing (or H 2 S‐producing) bacteria as well as other archaea and bacteria found in previous MEOR studies 17,41 . Common bacteria phyla include Proteobacteria, Bacteroidota, Firmicutes, Synergistota, Spirochaetota, Verrucomicrobiota, Desulfobacterota, and Campilobacterota, of which the latter three are prominent sulfur‐metabolizing bacteria 42–45 . These populations were distinct from others in the literature, 13,37 a finding that is not unexpected given that each community is driven by un environmental conditions such as temperature, salinity, pH, nutrient availability, and oil gravity among other factors 25 .…”
Section: Resultsmentioning
confidence: 48%
“…17,41 Common bacteria phyla include Proteobacteria, Bacteroidota, Firmicutes, Synergistota, Spirochaetota, Verrucomicrobiota, Desulfobacterota, and Campilobacterota, of which the latter three are prominent sulfur-metabolizing bacteria. [42][43][44][45] These populations were distinct from others in the literature, 13,37 a finding that is not unexpected given that each community is driven by un environmental conditions such as temperature, salinity, pH, nutrient availability, and oil gravity among other factors. 25 However, there is no known correlation between native microbial community and MEOR success.…”
Section: Wells Within the Same Basin Have Unique Properties And Micro...mentioning
confidence: 59%
See 1 more Smart Citation
“…2, S2). This interpretation is supported by the fact that microorganisms degrading chitin have been described in the FGL monimolimion (Rojas et al, 2021).…”
Section: Biological Mechanisms In the Fgl Whitingmentioning
confidence: 72%
“…They were recently also characterized as polysulfide reducers (Flieder et al, 2021), the distribution of which was reported to be driven by grain size and Cu and Cr concentrations in a high hydrocarbon-contaminated marine sediment in the Mediterranean Sea (Dell'Anno et al, 2021). The same positive correlation to methane detection with Chloroflexi and Elusimicrobiota indicates that these groups could be similarly involved in anaerobic hydrocarbon degradation via fermentation (Bovio-Winkler, Cabezas and Etchebehere, 2021), giving meaning to some groups included in the "microbial dark matter" found in anaerobic sulfidic systems, such as Elusimicrobiota (Rojas et al, 2021).…”
Section: Entrapped Methane and Methanogenesis In The Swacpmentioning
confidence: 88%